MIND SET OF PEACE CULTURE BASED ON AL QURAN VALUES TEACHERS AND STUDENTS OF MADRASAH ALIYAH - Budiman, Nandang; Hasbiyalah, Hasbiyalah; Tarsono, Tarsono (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
The mindset of peace culture based on the values of the Al Quran for teachers and students is the essential foundation for the realization of a peaceful school that is coveted by various parties.However, efforts to realize a peaceful school currently still have many obstacles so serious efforts are needed to make it happen. This study aims to explore the mindset of the peace culture of teachers and students of Madrasah Aliyah as a study towards developing the mindset of the school's peaceful culture. The research was conducted through a survey of 44 grade VIII students and 20 Madrasah Aliyah teachers in West Bandung Regency in 2021. The instrument used was a tool for measuring the mindset of peace culture based on the values of the Al Quran of teachers and students whose validity and reliability had been tested. The results showed that (1) both the development of mindset of peace culture based on the values of the Al Quran of teachers and students were in the moderate category and (2) there was no significant similarity between the mind set of peace culture based on the values of the Al Quran of teachers and students. The development of learning models that can facilitate the development of mindset of peace culture based on the values of the Al Quran for teachers and students is highly recommended.